Scaling up of CSA Platforms at the Subnational (District) Levels in Ghana: a Progressive Achievement of Theghana CCAFS Science-Policy Platform - Botchway, Vincent Ansah; Sam, Kingsley Odum; Karbo, Naaminong; Essegbey, George Owusu; Nutsukpo, Delali; Agyemang, Kingsley; Zougmoré, Robert B.; Partey, Samuel T. (Council for Scientific and Industrial Research, Ghana, 2016)
Globally the picture on climate change and its effects on humanity appear quite disturbing as food systems and consumption patterns are sliding towards low against prediction values. In Ghana population expansion as a driver has quadrupled now and calls for more food and fibre needs than ten decades ago (Karbo et al, 2015). The awareness of climate change on socio-economic development among development workers, scientists and policy decision makers appears high though more attention has been given to the search for biophysical solutions than the policy institutional environment enabling their uptake. The CCAFS programme in West Africa coordinated by ICRISAT, Bamako involving Ghana, Mali and Senegal was able to set up national multi-stakeholder platforms for sharing information on climate change and related policy issues. The platforms also provide a linkage mechanism between research, policy decision makers and community level actors in order to positively influence climate change investments and project trajectory in agriculture with effective adaptive, resilient and mitigation outcomes at the farmer level. The Ghana CCAFS Science –Policy Platform formation preceded with a meeting held in Burkina Faso in 2013 where a three member team from Ghana was involved with subsequent drafting and submission of proposal in request for funding leading to its establishment. The Ghana national climate change science policy platform as a multi-stakeholder institutional innovation came into being in 2013 with the support of CCAFS West Africa, set out to bridge science-policy literacy gap at the national and sub-national levels. In 2014, Ghana through the collaborative efforts of the national Platform implemented CCAFS Flagship4 activities which sought to deepen interaction at all levels. This culminated into the establishment of platforms at Lawra, Jirapa and Nandom districts with the view to strengthen climate change discourse, attitudinal change and actions at that level while maintaining a vibrant functional linkage mechanism with the national platforms for policy influence. An assessment of climate change policy and institutional context by Essegbey 2014, in these three districts, revealed that large gap exists between the national and subnational levels in terms of policy development and dissemination. The report identified weaknesses in harnessing societal grassroots inputs for policy formulation process and lack of awareness and knowledge about the policy especially in the decentralized levels of society in these three districts (Essegbey 2014). This suggests that policy literacy is very low and could pose challenge to effective implementation of the NCCP. The establishment of these platforms were necessary to help bridge the policy literacy gap. Today, these platforms provide soft landing for research activities and projects such ASSAR project, Water and Land Ecosystem project etc. The platforms also provide inputs into the districts level development annual plans. Effective networking with other local and international bodies have also been recognised. This info note seeks to give a process description of the scaling up of district sciencepolicy platforms in Ghana, the structures, the perceptions of the actors with particular reference to the platform, perceived functions, fears and organizational leadership diversities.